Kontra Terorisme Oleh Kepabeanan Indonesia PenyelundupanAmonium Nitrat - Putu Sanjaya, Yohanes Genius (UI Scholars Hub, 2019)
This paper examines the strategic role of Indonesian customs in the enforcement of ammonium nitrate smuggling as a concrete manifestation of its contribution in implementing counter-terrorism policies in Indonesia. David Omand (2006) says ―an effective counter-terrorist needs coherence of efforts among a wide variety of public and private sector bodies and this is best achieved by adopting a conscious process of strategic planning‖. Some of the best practices of counter-terrorism policies in Germany, the United States and the United Kingdom show that Customs involvement is vital because every country basically has the same goal of ensuring state security and the safety of citizens. The method used in this paper is a qualitative approach in the form of a case study of seizure of ammonium nitrate smuggling in Indonesia. The conclusion of this paper is that the Customs function is vital and strategic in overcoming the smuggling of ammonium nitrate as a form of contribution in preventing acts of terrorism as part of counter terrorism policies.